THE GRAMEENPHONE - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
The Grameen Bank in Bangladesh has incorporated ICTs in its proven system of micro-credit to groups of village women. The latest approach is to provide loans to women for the purchase of a mobile phone, which they can then rent out to villagers.The...